Bletilla striata oligosaccharides improve metabolic syndrome through modulation of gut microbiota and intestinal metabolites in high fat diet-fed mice. (September 2020) - Hu, Baifei; Ye, Cheng; Leung, Elaine Lai-Han; Zhu, Lin; Hu, Haiming; Zhang, Zhigang; Zheng, Junping; Liu, Hongtao
Graphical abstract: Highlights: Bletilla striata oligosaccharides (BO) improved HFD-induced metabolic syndrome. BO reversed gut microbiota dysfunction that is related to metabolic syndrome. BO partly repressed the disbalance of metabolite production by intestinal bacteria. Abstract: As traditional Chinese medicine, Bletilla striata has been widely applied to clinical treatment for its unique pharmacological profiles. This study aimed to investigate the beneficial role of Bletilla striata oligosaccharides (BO) in improving the metabolic syndrome by regulation of gut microbiota and intestinal metabolites. Treatment of HFD-fed mice with BO prevented weight gain, reversed the glucose intolerance and insulin resistance, and inhibited adipocyte hypertrophy. BO-treated mice also suppressed chronic inflammation and protected intestinal barrier from damage. These effects were linked to the reversal of gut microbiota dysbiosis, which contributed to the homeostasis of intestinal metabolites including bile acids, short-chain fatty acids and tryptophan catabolites. The depletion and reconstitution of intestinal flora from BO- or HFD-treated mice confirmed the significance of gut microbiota in regulation of HFD-induced metabolic disorders. We demonstrated for the first time that BO improved metabolic syndrome through the regulation of gut microbiota and intestinal metabolites. The modulation initiated by BO represents a promising strategy for treatment of obesity and related metabolic diseases.